CD200 and Chronic Lymphocytic Leukemia: Biological and Clinical Relevance - D’Arena, Giovanni; De Feo, Vincenzo; Pietrantuono, Giuseppe; Seneca, Elisa; Mansueto, Giovanna; Villani, Oreste; La Rocca, Francesco; D’Auria, Fiorella; Statuto, Teodora; Valvano, Luciana; Arruga, Francesca; Deaglio, Silvia; et al. (Frontiers in Oncology, 2020)
CD200, a transmembrane type Ia glycoprotein belonging to the immunoglobulin protein superfamily, is broadly expressed on a wide variety of cell types, such as B lymphocytes, a subset of T lymphocytes, dendritic cells, endothelial and neuronal cells. It delivers immunosuppressive signals through its receptor CD200R, which is expressed on monocytes/myeloid cells and T lymphocytes. Moreover, interaction of CD200 with CD200R has also been reported to play a role in the regulation of tumor immunity. Overexpression of CD200 has been reported in chronic lymphocytic leukemia (CLL) and hairy cell leukemia but not in mantle cell lymphoma, thus helping to better discriminate between these different B cell malignancies with different prognosis. In this review we focus on the role of CD200 expression in the differential diagnosis of mature B-cell neoplasms and on the prognostic significance of CD200 expression in CLL, where conflicting results have been published so far. Of interest, increasing evidences indicate that anti-CD200 treatment might be therapeutically beneficial for treating CD200-expressing malignancies, such as CLL.